Efektivitas Larutan Buah Belimbing Wuluh (Averrhoa blimbi) dalam Menurunkan Angka Kuman pada Sendok Makan - Putri Nabila; Nurul Amaliyah; Muhammad Rifqi Maulana (Buletin Keslingmas, 2026)
Hospital food safety is a crucial aspect of supporting the patient healing process. One frequent source of food contamination originates from unhygienic eating utensils, particularly spoons that come into direct contact with the patient's mouth. The use of plant-based disinfectants, such as bilimbi (Averrhoa bilimbi L.), which contains antibacterial compounds like flavonoids, has the potential to reduce the germ count on tableware. Therefore, this study was conducted to determine the effectiveness of bilimbi fruit solution at various concentrations in reducing the germ count on hospital spoons. This study employed a quasi-experimental method with a post-test-only with control group design. Data analysis using the One-Way ANOVA test yielded a significance value of 0.00 (p < 0.05), indicating a significant difference in the germ count on spoons across the various concentrations of bilimbi fruit solution: 0% (control), 10%, 15%, 20%, 25%, and 30%. Further post-hoc testing revealed that the 30% concentration demonstrated the highest efficacy in reducing the germ count on spoons, achieving an effectiveness rate of 97.63%. Future researchers are recommended to conduct studies using different concentration variations of bilimbi fruit solution to achieve an even higher reduction efficiency of germ counts on eating utensils.